Perspectives on language structure and language change: studies in honor of Henning Andersen - Heltoft, Lars; Igartua, Iván; Joseph, Brian D.; Kragh, Kirsten Jeppesen; Schøsler, Lene (Amsterdam studies in the theory and history of linguistic science, 2019)
Klappentext: This volume centers on three important theoretical concepts for the study of language change and the ways in which language structure emerges and turns into new structure: reanalysis, actualization, and indexicality. Reanalysis is a part of ongoing everyday language use, a process through which language is reproduced and changed. Actualization refers to the processes through which a reanalyzed structure spreads throughout single communities and society. Indexicality covers the way in which parts of a linguistic system can point to other parts of the system, both syntagmatically and paradigmatically. The inclusion of indexicality leads to fine-grained analysis in morphology, word order, and constructional syntax.
Keywords: Aufsatzsammlung; Festschrift; Sprachwandel; Andersen, Henning; Sprachbau